Forward and Reverse Osmosis Process for Recovery and Re-use of Water from Polluted Water by Phenol (Journal of Engineering, 2011)
The research aims to apply the novel forward osmosis (FO) process to recover pure waterfrom contaminated water. Phenol was used as organic substance in the feed solution, while sodiumchloride salt was used as draw solution. Membranes used in the FO process is the cellulosetriacetate (CTA) and polyamide (thin film composite (TFC)) membrane. Reverse osmosis processwas used to treatment the draw solution, the exterior from the forward osmosis process. In the FOprocess the active layer of the membrane faces the feed solution and the porous support layer facesthe draw solution and this will show the effect of dilutive internal concentration polarization andconcentrative external concentration polarization.In the FO process was a run-time for five hours, and the concentration of phenol 100 and1000 mg/l, and for the NaCl the concentration was 10000 and 30000 mg/l. It was found thatrecovery percent increases with increasing time, while water flux through membrane decreases withincreasing time. Also, it was found that recovery and water flux increases with increasing drawsolution concentration, on the contrary, water flux and the percentage of recovery decreases withincreasing the concentration of phenol (feed solution). Increase in draw solute (NaCl) concentrationhas more effect on the water flux in FO process compared with increase in the concentration ofphenol. Outlet phenol concentration increases with time, while the outlet salt concentrationdecreases with increasing the time. The results showed that the cellulose triacetate membrane gavethe highest recovery ratio from the thin film composite membrane. The highest recovery wasreached in five hours is 51.33%, while using CTA membrane recovery rate increase, by 23%compared with TFC membrane. The value of the resistance to solute diffusion within the membraneporous support layer is 36.83 h/m. Reverse osmosis is perfect method for removal of dissolved saltsfrom water, thus its suitable process for reducing the content of NaCl in draw solution; therefore thesodium chloride rejection percentage was 91.6 – 96 % for polyamide membrane (TFC). Within twohours of work of the reverse osmosis system the recovery percentage of pure water is 58%.